Speech at the opening of the courses of Bachelor of Library and Information Science at the School of Library Science at the National University March 4, 1991 - Bonilla Sandí, Albán (1991)
Speech by the Dean of the Faculty of Philosophy and Letters at the inauguration of the courses of the Bachelor's Degree in Librarianship and Documentation at the School of Librarianship of the National University.